2008
DOI: 10.14310/horm.2002.1203
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-adrenal responses following major abdominal surgery

Abstract: OBjeCTive: Perioperative pituitary-adrenal responses after major abdominal surgery have not been well characterized. The aim of the present study was to further clarify perioperative pituitary-adrenal responses. DeSiGN: Thirty-six patients (20 men), aged 68±10 years (mean±SD), undergoing major abdominal operations were studied. Total cortisol (TC), Adrenocorticotropic Hormone (ACTH), corticosteroid-binding globulin (CBG), dehydroepiandrosterone (DHeA) and its sulphate (DHeAS) were measured preoperatively (PreO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
1
12
1
6
Order By: Relevance
“…Dimopoulou et al . showed that CBG levels drop immediately after intra‐abdominal surgery, but recover by day 2 postoperatively . Postoperative total CBG levels at 474 nmol/l, however, remain higher than the levels seen in our patients with sepsis or septic shock; thus, we do not believe that surgery was a confounding influence in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Dimopoulou et al . showed that CBG levels drop immediately after intra‐abdominal surgery, but recover by day 2 postoperatively . Postoperative total CBG levels at 474 nmol/l, however, remain higher than the levels seen in our patients with sepsis or septic shock; thus, we do not believe that surgery was a confounding influence in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Dissociation between cortisol and ACTH levels following major surgery has been observed, particularly on the first postoperative day, whereas ACTH levels spread strongly immediately after surgery [23,37,40,41]. ACTH is produced primarily by the anterior pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Dimopoulou et al concluded that, at an early phase following major surgery, elevated cortisol is associated with high ACTH. [3] Wakim and Sledge et al…”
Section: Discussionmentioning
confidence: 99%